Thermal Hydraulic Performance of a Turbulent Wall Jet Flowing Over a Wavy Wall - Kumari A.; Kumar A. (My University, 2025)
The thermal and fluid flow characteristics of a two-dimensional turbulent wall jet have been studied numerically for the partial wavy wall. The partial wall is created by giving a segment of wall a wavy pattern from the leading edge followed by the plane wall; the wavy wall segment varies from 10% to 100% of the wall. The amplitude of wavy surface has also been varied from 0.2a to 0.8a with the interval of 0.2a, where “a” is the nozzle height. The results of the present problem have been compared with the results of a fully plane wall jet. The Reynolds number at the nozzle exit is constant, i.e., 15000 for all the cases to achieve fully turbulent jet. To solve this problem, low Reynolds number RNG model has been used. The results obtained from the present study show that the heat transfer rate remains almost the same for 10% to 100% wavy wall for 0.2a amplitude. In the case of amplitude 0.8a, the heat transfer rate is maximum for 30% wavy wall case; the heat transfer rate reduces further for higher wavy wall %. There is a 26.27% increment in heat transfer for the 30% wavy wall with 0.8a amplitude relative to the fully plane wall jet. The maximum increment in the thermal hydraulic performance (THP) of 5.3% is achieved for 70% wavy wall portion for 0.8a amplitude and it remains the same for further increase in the % of wavy wall. It must be noted here that earlier a 19.08% increase in average heat transfer is achieved for the wavy wall with an amplitude of 0.7 in the previous study. However, in this paper, an increase of 26.27% is noticed with the new design of wavy wall. This study will help in designing a highly efficient cooling or heating system in the engineering application by modifying just only the leading surface of the wall. Copyright VC 2023 by ASME.